Analisis Pengendalian Manajemen dalam Prosedur Penggajian pada UD. Surabaya Rambigundam Kabupaten Jember - Hindun Diah Safitri; Yuniorita Indah Handayani; Ihrom Caesar Ananta Putra (CV. ITTC INDONESIA, 2025)
This study aims to evaluate the management control system in the payroll process at UD. Surabaya Rambigundam, a garment manufacturing company located in Rambipuji District, Jember Regency. The background of this research stems from the complexity of the company's payroll system, which involves two types of employees (permanent and contract-based) and two payment methods (cash and bank transfer), including a wage advance policy that lacks formal documentation. This research employs a qualitative descriptive approach using a case study method. Data were collected through direct observation, in-depth interviews with management and employees, and analysis of company documentation. The results indicate that out of 16 control indicators examined, only five are properly implemented in practice. The main weaknesses identified include lack of task segregation, absence of formal authorization, poor documentation of policies, inadequate attendance tracking, and the absence of technology-based payroll systems. However, several strengths were noted, such as the availability of salary slips, dual-format payroll records (hard and digital), and an open communication culture between management and employees. The conclusion of this study emphasizes that the management control system at UD. Surabaya remains weak and requires comprehensive improvement, both structurally and technologically, to establish an efficient, accountable, and sustainable payroll system.